2013
DOI: 10.1308/003588413x13511609958578
|View full text |Cite
|
Sign up to set email alerts
|

Operative and non-operative management of endoscopic retrograde cholangiopancreatography-associated duodenal injuries

Abstract: INTRODUCTION Endoscopic retrograde cholangiopancreatography (ERCP) is indispensable in everyday surgical practice.Despite this, as an invasive procedure, it has its own mortality and morbidity, the most feared of which is periduodenal perforations. Our experience with ERCP related periduodenal perforations and its treatment strategies are presented. Additionally, a rarely encountered subtype is highlighted. METHODS Patients who underwent ERCP and sustained a periduodenal perforation between August 2008 and Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…(10,12,18,19). Mortality rates between 7% and 25% were reported in several studies, in which the most common types of perforations were type I and II (12,19,20). In our study, the most common type was type II injury (60%); only one patient with type I injury (5%) died of sepsis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…(10,12,18,19). Mortality rates between 7% and 25% were reported in several studies, in which the most common types of perforations were type I and II (12,19,20). In our study, the most common type was type II injury (60%); only one patient with type I injury (5%) died of sepsis.…”
Section: Discussionsupporting
confidence: 51%
“…Although emergency surgical treatment has been advocated in previous studies, conservative treatment was commonly reported with successful outcomes in appropriate cases in recent series. (10,12,18,19). Mortality rates between 7% and 25% were reported in several studies, in which the most common types of perforations were type I and II (12,19,20).…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of endoscopic perforations is higher for therapeutic procedures. The rate of duodenal perforations after ERCP ranges from 0.09 to 1.67% [26,27]. The Stapfer classification has been developed to categorize ERCP-related perforations [28].…”
Section: Endoscopic Perforationsmentioning
confidence: 99%
“…In most situations the approach should be individualized to the patient [71]. Multiple case reports of successful clip closure have been reported.…”
Section: Managementmentioning
confidence: 99%